Neurosurgical management of cerebellar haematoma and infarct. Issue 3 (September 1995) - Mathew, P; Teasdale, G; Bannan, A; Oluoch-Olunya, D
Abstract : The clinical features, treatment, and outcome were reviewed for 48 patients with a haematoma and 71 patients with an infarct in the posterior fossa in order to develop a rational plan of management. Clinical features alone were insufficient to make a diagnosis in about half of the series. Patients with a haematoma were referred more quickly to the neurosurgical unit, were more often in coma, and more often had CT evidence of brain stem compression and acute hydrocephalus. Ultimately, 75% of the patients with a haematoma required an operation. By contrast, most patients with an infarct were managed successfully conservatively. Early surgical management in both cerebellar haemorrhage and infarct (either external ventricular drainage or evacuation of the lesion), associated with early presentation and CT signs of brain stem compression and acute hydrocephalus, led to a good outcome in most patients. Of the patients with cerebellar haematoma initially treated by external drainage, over half subsequently required craniectomy and evacuation of the lesion; but, in some cases, this failed to reverse the deterioration. In patients with a cerebellar infarct, external drainage was more often successful. The guidelines, findings, and recommendations for future management of patients with posterior fossa stroke are discussed.